COMPONENTS OF KNOWLEDGE CONTROL (Scientific journal of the Fergana State University, 2024)
This article examines the relevance of the problem of knowledge control in the modern educational process and defines the main components of the concept of knowledge control in theoretical empirical research. As a result of the study, the principles and functions of knowledge control are determined. The methods, forms, types and types of pedagogical control in the educational process are classified.